Antioxidant Activity of Ethanol Extract of Breadfruit Peel (Artocarpus altilis (Park.) Fosberg) and Determination of Total Phenolic and Flavonoid Levels - Febriana Wahyuningtyas; Ibrahim Arifin; Khoirul Anwar (Jurnal Ilmiah Sains, 2025)
Breadfruit peel (Artocarpus altilis (Park.) Fosberg) contains phenolic compounds and flavonoids. These compounds have benefits as antioxidants. This study aims to determine the antioxidant activity of ethanol extract of breadfruit peel by using the ABTS (2,2- Azinobis (3- Ethylbenzothaizoline-6- Sulfonic Acid)  method and determining the total phenolic and flavonoid levels.  The skin of breadfruit is extracted using a method with a 96% ethanol solvent. The results of the extract were tested for antioxidant activity by ABTS and trolox methods as a comparison, and the total phenolic and flavonoid levels were determined by comparing gallic acid and quercetin using UV-VIS spectrophotometry. The results of the absorbance data were analyzed by linear regression to obtain IC₅₀ values. Total phenolic and flavonoid levels were expressed by mgGAE/gram extract and mgQE/gram extract.  The results showed that the extract ethanol of breadfruit peel extracted by maceration method obtained IC₅₀ 47.86±0.07 ppm, trolox IC₅₀ 20.17±0.06 ppm. The determination of the total phenolic and flavonoid levels was obtained as 280.70±2.54 mg GAE/gram and 5,51±0.02 mgQE/gram extract. Antioxidant activity of ethanol extract of breadfruit peel is categorized as a very powerful antioxidant. Keywords: antioxidants; breadfruit peel; flavonoids; phenolics